Alternatives assessment of perovskite solar cell materials and their methods of fabrication. (November 2020) - Llanos, M.; Yekani, R.; Demopoulos, G.P.; Basu, N.
Abstract: Perovskite solar cells have emerged as a new category of photovoltaics, gaining traction in the scientific community due to their high power conversion efficiencies, tolerance to material defects, and potential for scalable low cost manufacturing. Despite this, perovskite technology has been slow to commercialize in part due to toxic concerns of lead (Pb) in the benchmark composition CH3 NH3 PbI3, as well as the use of toxic solvents (e.g. dimethylformamide or chlorobenzene) used in perovskite film fabrication. To help identify safer alternatives, this study assessed 45 perovskite material alternatives to CH3 NH3 PbI3 (and their methods of fabrication) on the bases of ecological and human hazards, performance, and economic viability. This study followed the U.S. National Research Council's Framework to Guide Selection of Chemical Alternatives and thus collected and compared performance indicators, estimated levelized costs of energy (LCOE), and hazard data from 118 variables within 6 categories. In total, our analyses derived 38, 184 cells of data (36, 160 cells of hazard data, 1150 cells of performance data, and 874 cells of cost data). The best performing non-Pb-based perovskite was identified to be CH3 NH3 SnIBr2 synthesized via a mechanochemical fabrication approach. As the demand for affordable and competitive performing solar energy increases, this research could be utilized to inform and promote the sustainable development of this technology, ultimately guiding the entrance of perovskite solar cell materials into the photovoltaic market. Highlights: Perovskite solar cells gaining interest though concerns exist over toxic hazards. Alternatives assessments help identify safer options. 45 perovskite alternatives to the benchmark (CH3 NH3 PbI3 ) were evaluated. 38, 184 cells of data on toxic hazard, performance, and economic cost were compiled. CH3 NH3 SnIBr2 synthesized via mechanochemical fabrication was best non-Pb option.